Dragonslayer: musical composition and mythical thought - Irlandini, Luigi Antonio (Revista Vórtex, 2021)
The work Vá¹›trahan (2017), composed by Luigi Antonio Irlandini for baritone saxophone and percussion, creates a new relationship between musical and mythical thought, explored also in many of his other compositions since 1988. In this piece, the Vedic myth of Indra slaying the Cosmic Dragon Vá¹›tra suggests structuring procedures, instrumental sound sources and sound images, resulting on a congruency between the music and the myth far greater than a simple programmatic relationship. The discussion of some of the compositional processes in this work, as they were suggested by mythical thought, illustrates the composer's idea of composition as cosmology.